Optimisation of Remazol Brilliant Blue R dye decolourisation and laccase enzyme production by Marasmius cladophyllus using response surface methodology - Nur Adila, Muradi; Ahmad, Husaini; Azham, bin Zulkharnain; Hairul Azman, Roslan; Tay, Meng Guan (Malaysian Society of Applied Biology, 2017)
The decolourisation of Remazol Brilliant Blue R dye and laccase activity was investigated using pure culture of an endophytic fungus, Marasmius cladophyllus. The fungus is found capable of decolourising 99% of the dye after 12 days of incubation in Glucose Minimal (GM) liquid media (pH 5.5) and laccase activity of 285 U/L was recorded. Response surface methodology (RSM) was used to determine and optimise the significant variable(s) in order to obtain the optimum dye decolourisation conditions and laccase production. It was also used to study the interaction effect of the variables on both responses. Box-Behnken Design was used to identify the significant variable(s) whereas the optimisation process was done by using Central Composite Design. It was found that initial dye concentration of 100-300 mg/L, incubation period of 4-20 days and pH of liquid medium of 4-8 significantly influenced the decolourisation of dye and laccase activity. However, only the relationship of the incubation period and pH is significantly affected both the responses. Maximum dye decolourisation of 100% was successfully achieved and the highest laccase activity of 504.53 U/L was recorded after 16 days of incubation period at pH 7 with 259.46 mg/L initial dye concentration.